2003
DOI: 10.1093/bja/aeg106
|View full text |Cite
|
Sign up to set email alerts
|

Warming by resistive heating maintains perioperative normothermia as well as forced air heating † †None of the authors has personal financial interests related to this study.

Abstract: Resistive heating maintains core body temperature as well as forced air heating and both are better than circulating water. Resistive heating offers the advantage of adjustable heating pods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 11 publications
1
42
1
9
Order By: Relevance
“…10,15 In our study, we assessed the efficacy of 2 warming systems that are recommended for prewarming. The inflatable part of the forced-air cover (40 ϫ 105 cm) approximately equals the total surface of the carbon fiber elements incorporated in the resistive heating blanket (5 ϫ 40 ϫ 20 cm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,15 In our study, we assessed the efficacy of 2 warming systems that are recommended for prewarming. The inflatable part of the forced-air cover (40 ϫ 105 cm) approximately equals the total surface of the carbon fiber elements incorporated in the resistive heating blanket (5 ϫ 40 ϫ 20 cm).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Several reusable resistive-warming systems have been developed recently. 10,[12][13][14][15][16] They are based on carbon fiber technology and have a low-voltage, direct current power supply. In this study, we assessed the efficacy of a resistiveheating system or a forced-air warming system for 30 minutes of prewarming in comparison with a control group that received the current standard of care.…”
mentioning
confidence: 99%
“…[12][13][14][15] A number of studies, for example, have suggested the use of reflective technology as a prevention strategy. [16][17][18][19] Ensminger and associates 18 suggested that reflective technology had properties to preserve body temperature by reflecting the patient's radiant heat loss and also preventing convective heat loss to the cold OR.…”
Section: Discussionmentioning
confidence: 99%
“…Less heat is transferred to the operating room and staff, making it a more favourable environment in which to work. 46 Unlike FAW the blanket itself is less flexible, so it may not be directly adjacent to the patient's skin. 47 Current evidence suggests that there is little difference between FAW and resistive technologies in terms of preventing hypothermia.…”
Section: Warming Methodsmentioning
confidence: 99%